2019
DOI: 10.3389/fcell.2019.00159
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Crosstalk Between YAP1/Hippo Pathway and the p53 Family Proteins: Mechanisms and Outcomes in Cancer

Abstract: The YAP1/Hippo and p53 pathways are critical protectors of genome integrity in response to DNA damage. Together, these pathways secure cellular adaptation and maintain overall tissue integrity through transcriptional re-programing downstream of various environmental and biological cues generated during normal tissue growth, cell proliferation, and apoptosis. Genetic perturbations in YAP1/Hippo and p53 pathways are known to contribute to the cells’ ability to turn rogue and initiate tumorigenesis. The Hippo and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 99 publications
1
64
0
Order By: Relevance
“…Contrarily, it has been reported that tumor suppressors, including RASSF1A and p53, negatively regulate YAP by activating the Hippo kinase cascade. The loss of function mutations of RASSF1A or p53, contributes to increased YAP expression in cancers [ 74 , 117 ].…”
Section: Hippo/yap Singing Pathway In Nsclcmentioning
confidence: 99%
“…Contrarily, it has been reported that tumor suppressors, including RASSF1A and p53, negatively regulate YAP by activating the Hippo kinase cascade. The loss of function mutations of RASSF1A or p53, contributes to increased YAP expression in cancers [ 74 , 117 ].…”
Section: Hippo/yap Singing Pathway In Nsclcmentioning
confidence: 99%
“…The activation of the Hippo signaling pathway is characterized by the upstream kinase-induced phosphorylation of its downstream effectors, including YAP1, resulting in the nuclear exclusion of YAP1, and ultimately, its cytoplasmic degradation. 26,27 Taken together, the aforementioned findings indicated that circTADA2A could downregulate miR-129-5p, thereby enhancing YAP1 and TRPS1 expression. However, miR-129-5p downregulation prevented the phosphorylation of YAP1 and its cytoplasmic degradation, thus contributing to OS cell proliferation and drug resistance.…”
mentioning
confidence: 74%
“…Recent researches have pointed to an important role for YAP1 signaling in tumor progression [30]. As the wellcharacterized downstream transcriptional coactivator of the Hippo pathway, YAP1 has been demonstrated to be highly activated in many tumors.…”
Section: Discussionmentioning
confidence: 99%